KETIDAKPASTIAN GLOBAL DAN TANGGAPAN PENDIDIKAN TINGGI HUKUM - Shidarta, Shidarta (Faculty of Law, Parahyangan Catholic University, 2022)
This article is a commentary to President Joko Widodo’s message in a speech given at the celebration of the UNPAR’s dies natalis in 2022, i.e. that manager of higher education institutions should adequately anticipate global uncertainty caused by the advance of industrial society 4.0 and the resulting technological disruptions. The comments given is made based on two different perspectives: legal scholars or academics n and practicing lawyers. In any case, those responsible for the management of higher education should respond to global uncertainty by developing skills to manage big data and other strategic steps.